Efektifitas Metode BC dan VEN Terhadap Perencanaan Obat di RSUD Praya Kabupaten Lombok Tengah Tahun 2022 - Abdurrahman Abdurrahman; Menap Menap; Lalu Jupriadi (Universitas Borneo Lestari, 2023)
The hospital is a health service agency in charge of organizing individual health services that provide inpatient, outpatient, and emergency services. To see the success of drug planning, it is necessary to evaluate using the ABC-VEN method. The analytical method used is descriptive analytic method with the ABC-VEN method using quantitative data that is available at the Praya Regional General Hospital so that this study is a retrospective study. The results showed that of the 566 drug items planned by the hospital, it was known that the drugs included in the (P) category were 149 drug items or about 26.3% of the total drug items. Main Category (U) about 395 drug items or 69.8% of the total drug items. Additional Category (T) as many as 22 items or about 3.9% of the total drug items. In addition, drug planning activities at Praya Hospital are carried out based on the consumption method which is carried out every month, supported by independently managed sources of funds.